Evaluation To Clean And Healthy Living Behavior (Phbs) On Students In SDN Sukalila Serang City-Banten - Rini Kundaryanti; Hanny Hanny (MBUnivPress, 2022)
The results of the PHBS measurement in schools consist of 8 indicators, namely: washing hands in running water with soap, using toilets and running water, exercising, eradicating mosquito nests, smoking behavior, weighing and measuring height every semester, disposing of garbage properly according to the place. This study aims to evaluate the behavior of school children towards cleanliness and health in Sukalila elementary school, Serang-Banten City. This study used a cross sectional design. Sampling was done by purposive sampling. In the results of the study, it was seen that school children who had PHBS were less than 60% and based on the results of the chi square test, there was a relationship between knowledge, attitudes, teacher roles with PHBS in school children and there was no relationship between gender and PHBS in school children at SDN Sukalila Serang City. -Banten with p value 0.15 > 0.05